Liposuction Assisted Abdominoplasty: An Enhanced Abdominoplasty Technique - Daniel Brauman, MBBS, MD, FACS; Rene R. W. J. van der Hulst, MD, PhD; Berend van der Lei, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2018)
Background:. Combining liposuction with abdominoplasties was considered risky during the 1980s and 1990s due to reports of increased complications rates and the belief that liposuction posed a danger to flap circulation. However, the corresponding author’s intraoperative observations at that time, that liposuction preserved all but the smallest blood vessels, negated the prevailing opinions that liposuction increased the risk to flap circulation, and in October 1996, liposuction assisted abdominoplasty (LAA) was first performed. Thereafter, LAA was honed to become a lipoabdominoplasty technique—not merely a combination of liposuction and abdominoplasty, a technique that utilizes liposuction as a dissection tool—hydro- and lipo-dissection, to dissect free and separate the abdominal flap from the deep fascia. Enhanced flap excursion could be demonstrated intraoperatively by selectively transecting the skin retaining ligaments and limiting liposuction to the flap’s undersurface, created a vascular lining layer rich in anastomosing blood vessels that provided a rich blood supply to the flap, enabling increased flap excursion. Methods:. Five ninety-three consecutive ambulatory LAAs with circumferential torso liposuction and other area liposuction are presented and the surgical technique is illustrated and discussed. Results:. There were no serious adverse events, anesthesia complications, hospital transfers, no venous thromboembolism or postoperative respiratory complications in the 593 cases. Patient satisfaction was high, and the results compared favorably with abdominoplasty results published in the scientific literature. Conclusions:. LAA is a safe and effective abdominoplasty technique. Extensive clinical experience with LAA suggests longer flap excursion and improved perfusion. It routinely incorporates circumferential torso and other areas liposuction and has commonly included buttock fat grafting.